Writing Under Pressure : the Quick Writing Process. - Kaye, Sanford (Oxford paperbacks., 1988)
Most writing is done under pressure. An executive has to produce a three-page position paper by tomorrow at nine. A department head suddenly has to write a one-page action memo by noon. A graduate student has a twenty-page research paper due in a week. Yet, while most students and professionals write under pressure--with limited time, limited space, and a supervisor or instructor to please--few approach the task systematically. In Writing Under Pressure, Sanford Kaye, a renowned expert on the subject, presents a system he calls the Quick Writing Process (QWP) that focuses on real-world writing.